ʺMethods of developing an individual educational trajectory for computer specialists in non-formal educationʺ - Lysenko, S. (Problems of Engineer-Pedagogical Education, 2024)
The article presents the method of forming an individual educational trajectory of computer specialists in the conditions of informal education. The impact of digitization rates on the development of technology and equipment is highlighted, which led to the formation of a key trend of educational policy - lifelong learning. It has been proven that one of the mechanisms of its implementation is involvement in the system of non-formal education. The peculiarities of the professional activity of computer specialists are outlined, which motivate them to constant professional and personal development in accordance with the requirements of dynamic changes in the content and technologies of work. Attention is paid to the characteristics of informal education and it is determined that its key feature is the student's independent choice of content, forms and methods of acquisition, respectively, the development of an individual educational path. The analysis of sources of information regarding the definition of the essence and structure of an individual educational trajectory was carried out. The method of its formation through the implementation of the following stages is presented: determination of the goal of educational activity, means of achieving it and correlation of one's capabilities, needs, and qualities with the requirements of the goal; formation of a priority complex of theoretical knowledge, practical skills and professionally important qualities that must be formed; determination of possible ways of obtaining education; analysis of possible results of informal education according to indicators (general satisfaction with the learning process, promotion of career development, development of professional competence and formation of professionally important qualities). The research method was the study and analysis of publications on the problem of developing an individual educational trajectory. The work shows the components of the methods of forming the individual final trajectory of specialists in a computer profile, so specialists of the specified profile will find useful theoretical and practical recommendations for use in their educational activities.